Laser-wakefield acceleration of electron beams in a low density plasma channel - Ibbotson, T; Bourgeois, N; Rowlands-Rees, T; Caballero, L; Bajlekov, S; Walker, P; Kneip, S; Mangles, S; Nagel, SR; Palmer, C; Delerue, N; Doucas, G; et al. (2010)
The generation of quasimonoenergetic electron beams, with energies greater than 500 MeV, in a laser-plasma accelerator driven by 2.5 J, 80 fs laser pulses guided in a low density plasma channel, is investigated. The laser energy required to achieve electron injection is found to depend strongly on the quality of the input laser focal spot. Simulations show that, although the matched spot size of the plasma channel is greater than the self-focused spot size, the channel assists relativistic self-focusing and enables electron injection to occur at lower plasma densities and laser powers than would be possible without a waveguide. © 2010 The American Physical Society.